Analisis Pengembangan Kompetensi Baca Al-Qur’an Sesuai Konsep dan Kaidah Qiraah Melalui Strategi Pembelajaran Problem Based Learning - Abdul Aziz; Yulia Warda; Nurul Hidayah; Muhammad Zali (Sekolah Tinggi Agama Islam Sumatera Medan, 2022)
This study aims to analyze the development of students' Al-Qur'an reading competence according to the rules of Qiraah through Problem-Based Learning learning strategies. The research focuses on teachers' understanding of the implementation of learning, learning outcomes, and implementation constraints. This study uses a qualitative research method, a case study approach. The research location at MTs. Hifzhil Qur'an North Sumatra Islamic Center Foundation. The research location has become a centre for learning the Koran, which is popular in Medan and even North Sumatra. Research informants, namely teachers of Al-Qur'an Hadith lessons and eighth-grade students. Collect data using observation, interviews, and documentation studies. The study results show that the implementation of learning the Qur'an with qiraah rules uses a problem-based learning strategy in which the teacher determines one maqra' (reading) to be read by students. Students analyze the maqra', in which part of the sentence there is farsy al -letters and changes to Qawa'id Al-Ushuliyyah. Learning with these learning strategies can improve students' abilities. 85% of students can achieve learning completeness. However, in its implementation, there are obstacles, such as the lack of students' analytical skills and the number of students who are not proportional to the available study time.